PENGARUH PENGETAHUAN PENCATATAN AKUNTANSI TERHADAP PERTUMBUHAN EKONOMI DENGAN MODAL USAHA SEBAGAI VARIABEL INTERVENING - DEANITA SARI; Gayatri Nahdiyah Husen (Fakultas Ekonomi, Program Studi Akuntansi, 2020)
The Micro- Small and Medium Enterprises (MSMEs) are the highest economic egents in East Nusa Tenggara, which are able to absorb a workforce of 99.45%. Therefore, this study will be based on knowledge of accounting records for economic growth of MSMEs with interverning variables of business capital, which is considered capable for improving MSME economic growth in Kupang city. This study took a sample of 140 MSME entrepreneurs which are located around the natural tourism object at coastal of Kupang City with purposive sampling method using MSME Economic Growth as a Dependent Variable, Knowledge of Accounting Recording as Independent Variable, Business Capital as an Intervening Variable, and Gender, Age, Education Level, Type of Product, Long Time of Business as Control Variables.The results showed that knowledge of accounting records has a significant positive effect on working capital. Second, business capital has no effect on the economic growth of MSMEs. Third, knowledge of accounting records directly affects the economic growth of MSMEs and knowledge of accounting records has no effect on the economic growth of MSMEs with business capital as an intervening varisssable.